Applied sport psychology: A profession? - Winter, S.; Collins, D. J. (The Sport Psychologist, 2016)
Although the field of applied sport psychology has developed, it faces further challenges on its way toward gaining greater professional status. The following principal criteria of professionalism are proposed as a test of such status: (a) provides an important public service, (b) has a knowledge-base underpinning, (c) has organizational regulation, (d) has a distinct ethical dimension, and (e) has professional autonomy. This article undertakes to explore the nature of implications for practice and the extent to which the suggested principal criteria justify a distinctive applied sport psychology profession. In doing so, we hope to stimulate debate on these and other issues in order that an even greater professionalization of our applied discipline may emerge.